Erasing hell : what God said about eternity and the things we made up - Chan, Francis, 1967-; Sprinkle, Preston M., 1976- (Colorado Springs, CO : David C Cook, 2011)
How could a loving God send people to hell? Will people have a chance after they die to believe in Jesus and go to heaven? With a humble respect for God's Word, Francis Chan and Preston Sprinkle address the deepest questions you have about eternal destiny. They've asked the same questions. Like you, sometimes they just don't want to believe in hell. But as they write, "We cannot afford to be wrong on this issue." This is not a book about who is saying what. It's a book about what God says. It's not a book about impersonal theological issues. It's a book about people who God loves. It's not a book about arguments, doctrine, or being right. It's a book about the character of God. Erasing Hell will immerse you in the truth of Scripture as, together with the authors, you find not only the truth but the courage to live it out. - Back cover.
Addressing a variety of views on hell, the Bible, and the character of God, offers an eloquent response to the recent media storm surrounding questions of eternal destiny.
Does everyone go to heaven? -- Has hell changed? Or have we? -- What Jesus actually said about hell -- What Jesus' followers said about hell -- What does this have to do with me? -- What if God --? -- Don't be overwhelmed -- Appendix. Frequently asked questions.
Includes bibliographical references (pages 165-171).
Keywords: Hell -- Christianity; Hell -- Biblical teaching; Future life; Christian life; Nonfiction